„TRZECIA KULTURA” W DOBIE POSTHUMANIZMU I TRANSHUMANIZMU - Gajewska, Grażyna (Studia Europaea Gnesnensia, 2018)
Since the mid-twentieth century, there has been a discussion in the academy about “two cultures”: humanities and sciences and the so-called third culture. In this article I outline the history of this debate. I also present new trends in contemporary humanistic reflection: posthumanism and transhumanism, which are based on interdisciplinary research. I am also describing the projects and the output of several currents of contemporary art: robotic art, bio art and bio-robotic art.